PENGARUH EDUKASI DAN LITERASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR DI SAMSAT KOTA TANGERANG TAHUN 2022-2024 - Lisa Arisa Fiatri; Fani Julian Hasani (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to evaluate the extent to which tax education and tax literacy influence taxpayer compliance in paying Motor Vehicle Tax (PKB) within the jurisdiction of the Samsat Office in Tangerang City. The increase in PKB arrears during the 2022 to 2024 period indicates a compliance issue that is likely related to the public’s limited understanding of their tax obligations. This research applies a quantitative approach using a survey method by distributing questionnaires to 100 respondents who are motor vehicle taxpayers. Tax education and tax literacy are used as independent variables, while taxpayer compliance serves as the dependent variable. The data were analyzed using multiple linear regression with the help of SPSS software. The findings show that both tax education and tax literacy have a positive and significant effect on taxpayer compliance, both partially and simultaneously. This suggests that improving the quality of tax information and enhancing taxpayers’ ability to understand and use digital tax services such as the SIGNAL application and E Samsat can encourage timely and compliant tax behavior. Therefore, it is important for local governments and relevant institutions to continue developing effective and structured tax education and literacy programs as an effort to optimize PKB revenue which is a major component of Regional Original Revenue (PAD).